2022
DOI: 10.1186/s12891-022-06092-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical application of finite elements in the orthopedics of stiff clubfoot

Abstract: Background The purpose of this study was to evaluate the effect of varying the different correction angles of hindfoot osteotomy orthosis on the biomechanical changes of the adjacent joints after triple arthrodesis in adult patients with stiff clubfoot to determine the optimal hindfoot correction angle and provide a biomechanical basis for the correction of hindfoot deformity in patients with stiff clubfoot. Methods A 26-year-old male patient with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A static standing simulation was carried out using the FE model. In the standing state, each foot bears one-half of the gravitational force ( Bocanegra et al, 2021 ), and only the triceps of the calf has an obvious EMG signal ( Liu et al, 2022 ). Studies show that the force of the Achilles tendon is 50% of the force of the entire foot ( Sun et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A static standing simulation was carried out using the FE model. In the standing state, each foot bears one-half of the gravitational force ( Bocanegra et al, 2021 ), and only the triceps of the calf has an obvious EMG signal ( Liu et al, 2022 ). Studies show that the force of the Achilles tendon is 50% of the force of the entire foot ( Sun et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The strength of the triceps surae muscle was estimated only by extracting the strength of the Achilles tendon in the sagittal plane of the foot from inverse dynamics data. However, according to EMG data [52,53], when standing with both feet balanced, except for the triceps crus, other foot and lower-limb muscles showed no evident activity, which could be considered a lack of active contraction. Moreover, Simonsen et al [54], and Croin et al [55] demonstrated that the triceps crus is the main part that exerts the plantar flexion moment of the foot at pushoff during running.…”
Section: Limitationmentioning
confidence: 96%